2013
DOI: 10.1111/jace.12312
|View full text |Cite
|
Sign up to set email alerts
|

Structural and Dielectric Properties in (1−x)BaTiO3xBi(Mg1/2Ti1/2)O3 Ceramics (0.1 ≤ x ≤ 0.5) and Potential for High‐Voltage Multilayer Capacitors

Abstract: Structural and dielectric properties of (1−x)BaTiO3–xBi(Mg1/2Ti1/2)O3 (x = 0.1–0.5) were investigated to understand the binary system and utilize it for high‐voltage, high energy density capacitors. The solubility limit for Bi(Mg1/2Ti1/2)O3 in a BaTiO3 perovskite was between x = 0.4 and x = 0.5. A phase with pseudocubic symmetry was formed for x = 0.1–0.4; a secondary phase developed at x = 0.5. Dielectric measurements showed highly diffusive and dispersive relaxor‐like characteristics from 10 to 40 mol% of Bi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
39
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 88 publications
(44 citation statements)
references
References 22 publications
(51 reference statements)
5
39
0
Order By: Relevance
“…The similar phenomena were also reported in BaTiO 3 -BiMeO 3 systems. 31,32 The data at 1 MHz were used to evaluate any space charge polarization contributions to the permittivity at lower measurement frequency. The maximum permittivity (e m ) and the temperature of permittivity peak (T m ) at 1 MHz of ceramics are shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The similar phenomena were also reported in BaTiO 3 -BiMeO 3 systems. 31,32 The data at 1 MHz were used to evaluate any space charge polarization contributions to the permittivity at lower measurement frequency. The maximum permittivity (e m ) and the temperature of permittivity peak (T m ) at 1 MHz of ceramics are shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The low temperature dependence of the dielectric properties for the pseudocubic phase is in good agreement with previous reports for sintered bodies formed using BaTiO 3 -BiMO 3 solid solutions. [13][14][15][16][17][18][19] This is considered to be related to the relaxed behavior of these solid solutions, and the diffused temperature dependence of ε r , which reduces the overall temperature dependence of ε r . 20 In contrast, Mitsui et al reported that the maximum ε r was observed at more than 400 • C for x = 0.60.…”
Section: Methodsmentioning
confidence: 99%
“…11,12 Also, a low ε r temperature dependence has been reported for solid solution systems of BaTiO 3 and Bi-based perovskite oxides with pseudocubic structures at room temperature. Sintered bodies of BaTiO 3 -BiMO 3 [where M = Sc 3+ , Al 3+ , (Mg 0.5 Ti 0.5 ) 3+ , and (Zn 0.5 Ti 0.5 ) 3+ ] with pseudocubic symmetry show particularly high ε r stability at temperatures up to 400 • C. [13][14][15][16][17][18][19] In a previous study, we investigated the dielectric properties of ternary BaTiO 3 -Bi(Mg 0.5 Ti 0.5 )O 3 -BiFeO 3 solid solution films prepared by chemical solution deposition (CSD) as alternatives to BaTiO 3 -based high-ε r materials. 20 This system has a wide compositional region with a pseudocubic symmetry between the tetragonal and rhombohedral symmetries at room temperature.…”
Section: Introductionmentioning
confidence: 99%
“…Values of tan were ≤ 0.02 (100 KHz) from 270 to 550ºC, and ≤ 0.02 at 1 kHz for the narrow temperatures range 230-300ºC. Choi et al, investigated (1-x)BT-xBMT bulk ceramics and multilayer capacitors (20×129 µm layers) [24]. They found the solubility limit of BMT to occur around x = 0.4-0.5.…”
Section: Batio3-bi(mg05ti05)o3mentioning
confidence: 99%